Astro-Ethnobiology: Insects, Identity, and the Design of Food Systems in Space - Berggren, Åsa; Svanberg, Ingvar (Ethnobiology Letters, 2025)
Astro-ethnobiology—an explicitly interdisciplinary framework connecting ethnobiology and astrobiology—treats space food systems as cultural and ecological interfaces, not just technical solutions, by integrating engineering, bioregenerative ecology, and human factors. As humanity prepares for long-duration missions beyond Earth, these systems must support not only survival, but also identity, multispecies relations, and emotional resilience. Drawing on historical provisioning strategies, from maritime voyages to polar expeditions, we examine how animals fulfilled multifunctional roles in sustaining morale, routine, and ecological balance under extreme conditions. Insects, in particular, emerge as promising candidates for space-based life support due to their efficiency in nutrient provision and recycling as well as waste conversion. Beyond their biological utility, insects may contribute to psychological well-being and cultural continuity through care-based routines, storytelling, and sensory engagement. While cultural acceptance of insects as food remains a challenge in some parts of the world, historical dietary shifts show that unfamiliar foods can gain acceptance through ritual and shared experience. Astro-ethnobiology invites us to see space food not as a technical product, but as a shared practice shaped by care for other species, cultural meaning, and symbolic connection.